Komunikasi Interpersonal Dokter dan Pasien Gigi dan Mulut dalam Tindakan Pre dan Post Operasi Gigi dan Mulut di RSUD Dr. Soetomo Surabaya - Edelweis Putri Prima (Jurnal Spektrum Komunikasi, 2018)
The research entitled “Interpersonal Communication Between Doctor and Dental and Oral Patients during Pre-and Post-Treatment of Dental and Oral Surgery at RSUD Dr. Soetomo Surabaya”. Aims at finding out the process of interpersonal communication between oral surgery and the maxillofacial doctor and dental and oral surgery patient. This research is qualitative in nature with 3 informant patients of dental and 3 dentists. The data collection techniques are observation, in-depth interviews, and literature studies. The formulation of the research question is how the interpersonal communication between doctor and dental and oral patients during pre and post-treatment of dental and oral surgery is. The result of this research is the pre and post interpersonal communication which positively gives an important impact on patients, dentists, and family of patients. Positive communication proves to have an advantageous impact while negative communication even can cause a negative impact both to the dentist and to patients. There are many ways to improve the effectiveness of interpersonal communication between doctor and patients. However, there are some easy ways to create effective communications: positiveness, empathy, supportiveness, equality and openness. It is suggested that the patient and family of the patient be more active in asking about what to do for the pretreatment of dental and oral surgery. And in bringing out pains and impacts of post-dental and oral surgery to the doctor. For the specialist dentists of oral surgery and maxillofacial who perform the operation, he or she should work cooperatively and inform the patient and patient family actively so that communication between dentist and patient can go positively and effectively.